2010
DOI: 10.1007/s10439-010-9914-8
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the Influence of Compression on Artery Wall Mass Transport

Abstract: The development of restenosis within the coronary arteries after a stenting procedure has been addressed with the development of the drug eluting stent device. However, in recent times the superiority of the drug eluting stent over bare metal stents has been brought into question. A lack of knowledge regarding the behavior of drug transport from the drug eluting devices contributes to this uncertainty. Questions arise as to whether drug eluting stents deliver sufficient amounts of therapeutic agents into the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…However, the concentration is all time higher (x = 0.85) throughout the depth of the arterial wall just beneath the strut. This observation is in good agreement with those of [32]. Figure 4b shows the results of concentration profiles for different Pe.…”
Section: Resultssupporting
confidence: 79%
“…However, the concentration is all time higher (x = 0.85) throughout the depth of the arterial wall just beneath the strut. This observation is in good agreement with those of [32]. Figure 4b shows the results of concentration profiles for different Pe.…”
Section: Resultssupporting
confidence: 79%
“…What Model 3 demonstrates is that even a 20µm thick layer of plaque between the stent and the artery wall can significantly reduce uptake within the artery wall, even more so than arterial compression. The influence of compression on a porous wall in relation to mass transport has been demonstrated experimentally by O'Connell and Walsh (2010) and is evident in the results from Models 4 and 5. Histological evidence demonstrated that upon stent implantation some struts almost cut into the wall (Model 4) while others merely compress it providing gradual recovery either side of the stent strut (Model 5).…”
Section: Computational Predictions Of Mass Transport In the Artery Wallmentioning
confidence: 74%
“…In all published research to date, to the best of the researchers' knowledge, the change in the structure of the artery wall under stent compression and its subsequent effect on drug MT have not been modelled computationally. However O'Connell and Walsh [62] have demonstrated this effect in an analogous porous material, which indicates that artery wall compression should be present in all DES computational models. Stent strut thickness may be vital in minimising the extent of arterial compression after DES expansion.…”
Section: Porous Mediamentioning
confidence: 99%
“…A reported difference of 60 μm in strut thickness between two different stents used in the SPIRIT-III trial may not necessarily result in 60 μm further compression due to the elastic nature of the artery. However an exploration into the extent of compression on the artery wall due to stenting would exhibit changes in arterial diffusivity compared to the case of a relaxed artery [62]. This can be attributed to a reduction in porosity coupled with an increase in tortuosity (equation 1) within the artery wall beneath the stent strut.…”
Section: Porous Mediamentioning
confidence: 99%